Effect of various sugar solution concentrations on characteristics of dried candy tomato (Lycopersicum esculentum) - WAWAN BUNTARAN; OKID PARAMA ASTIRIN; EDWI MAHAJOENO (Smujo International, 2010)
Abstract. Buntaran W, Astirin PA, Mahajoeno M. 2009. Effect of various sugar solution concentrations on characteristics of dried candy tomato (Lycopersicum esculentum). Nusantara Bioscience 2: 55-61. The aims of the research were to study the effects of sugar syrup concentration on dried candy tomato characteristics and to determine the proper sugar solution concentration that gives the best characteristics of dry candy tomatoes. The research used Randomized Block Design Method with four treatments and six times repetitions. The treatment that be used was immersing the tomato in sugar solution, with concentration of A (40%), B (50%), C (60%), and D (70%) group in 18 hours. The variables measured were water content, ash, vitamin C and organoleptic tests include flavor, color, flavor and texture test. Data were analyzed using ANOVA test (Analysis of Variance) followed by DMRT (Duncan Multiple Range Test). The result showed that sugar solution concentration had different effect on water content, ash content, vitamin C content, texture, and organoleptic test for color, taste, and flavor of the dry candy tomato. The best characteristics of dry tomato candy was obtained on A (40%) group, with water content of  24.20%, ash content of 0.62%, and vitamin C content of 31.15 mg/100 g.  Standard quality of water content for dry fruit candy was maximal 25% (SII No.0718-2003) and maximally allowed ash content for food materials was 1.0% (SII 0272.90).  Vitamin C content was not much decreased compared with ripe tomato, i.e. 30-40 mg/100. Organoleptic tets result indicated that A (40%) group get the highest score, i.e. 3,98 for taste, 3,89 for flavor, and 3,98 for color.